DIAMAS: Supporting high quality Diamond Open Access publishing - Mounier, Pierre; Aspaas, Per Pippin (Open Science Talk, 2023)
In this episode, we are discussing the project Developing Institutional Open Access Publishing Models to Advance Scholarly Communication, in short: DIAMAS. At the heart of the project is support for Diamond Open Access, i.e. free for the reader as well as the author (no publishing charges). Co-lead of DIAMAS, Pierre Mounier explains the importance of lending support to not-for-profit institutional publishing. Besides the diversity offered by such scholar-led, high quality publication outlets, the multilingualism that they represent is key when the dissemination of knowledge and the promotion of citizen science across Europe is taken into account. The Helsinki Initiative on Multilingualism in Scholarly Publishing lends verbal support to linguistically diverse scholarly outputs; the EU-funded DIAMAS Project paves the way for stronger and more sustainable infrastructures facilitating them. Since its inception in September 2022, the project will last for 3 years. An ultimate goal of DIAMAS is to help the providers of publishing services raise the quality and visibility of diamond open access by establishing a Europe-wide capacity center. A sister project, CRAFT-OA, focusing on the purely technical aspects of institutional diamond open access publishing begins in January 2023. The preliminary Diamond OA Journals Study (published March 2021), the first ever global survey of diamond open access journals, serves as foundation for both projects. The recording was made in conjunction with the Munin Conference on Scholarly Publishing in December 2022. First published online January 10, 2023.